Influence of Social media advertisements on food purchasing behaviour among young adults - Menaka, S. (The Open University of Sri Lanka, 2022)
Food processing and distribution are deeply influenced by tradition; however intensive innovations lead to changes in the way individuals consume. One of these changes is the consistent growth of the habit of eating outside the home. Technology has made the purchase convenient for people. Advertisements are used to promote the goods and services that the market wishes to sell to the public. Advertising is one of the main modes of marketing. They entice customers to buy by using appealing images and sentences. These days a lot of advertising tools are being used to sell products. Social media plays a major role in advertisements, especially for marketing food items. Social media platforms become efficient sources to attract more customers. With the rapid growth of technology, young adults access social media anytime anywhere. This study was aimed at exploring the influence of social media face book advertisements on the food purchasing behaviour of young adults and how people react to social media advertisements. The respondents were young adults (21-30 years old) in the Jaffna district. A questionnaire was distributed to randomly selected participants including students, employees and unemployed persons from the district. Out of 234 respondents (111 male and 123 female) 83% purchased food because of social media advertisements. Attracted by the picture in the advertisement made up 61% of the purchasers. Participants consider reviews made by the consumers before purchasing (33%). When there are price reductions or coupons available in the advertisements, 57 % of the participants purchase food items. However, 38% of the purchasers felt that money was wasted on a particular order. With the wide use of the internet on smartphones, the advertisements can reach the consumers easily and the purchase of food items increases. During the Covid-19 Pandemic, people purchase food items online using advertisements due to lock down, travel restrictions and fear of exposure to illness in the outside world. Social media changes the traditional way of marketing by helping the consumers to purchase food from home easily. As young adults show poor healthy food purchasing behaviour the study recommends that the social media advertisements should focus on marketing of healthier food.
Keywords: Advertisement; Young adult; Social media; Food purchase